2003
DOI: 10.1023/a:1024608730471
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Oral treatment with lycopene (per os) in doses of 10 or 50 mg/kg for 2 weeks led to accumulation of lycopene in the liver, liver microsomes, and blood plasma, increased total plasma antioxidant activity, inhibited LPO in the liver, and decreased solubilization of lysosomal enzymes. Lycopene had no effect on ex vivo resistance of liver microsomes to LPO and activities of antioxidant enzymes in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…It can be hypothesized that the decrease in tripeptide concentration is related to activation of glutathione S-transferase. Similar changes were revealed in the cytosolic fraction of rat liver homogenates after 2 weeks of treatment with DHQ in a dose of 130 mg/kg [3].…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…It can be hypothesized that the decrease in tripeptide concentration is related to activation of glutathione S-transferase. Similar changes were revealed in the cytosolic fraction of rat liver homogenates after 2 weeks of treatment with DHQ in a dose of 130 mg/kg [3].…”
Section: Resultssupporting
confidence: 72%
“…Recent studies showed that DHQ has no genotoxic activity [1]. Most studies of biological activity (e.g., antioxidant properties) were performed in vitro on model systems [3,4,8,9]. Little is known about in vivo properties [3,10] and long-term effect of DHQ [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies [29,30] have suggested that lycopene is not detectable in the liver of animals consuming a normal diet without lycopene supplementation. However, lycopene supplementation causes a dose-dependent accumulation of lycopene in liver tissue, which was similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that intake of tomatoes and tomato products strengthened the antioxidant system, and inhibited lipid peroxidation in humans [12]. Besides, it was demonstrated that oral lycopene administration for 2 weeks inhibited lipid peroxidation in the liver tissues of rats [13]. The objective of present study was to investigate the protective effect of lycopene on the development of steatohepatitis in NASH model induced by HFD.…”
Section: Introductionmentioning
confidence: 94%